HOW TO ESTABLISH RELATIONSHIPS IN THE TWENTY-FIRST-CENTURY UNIVERSITY - Rodríguez Wong, María Teresa (2014)
The article supports proposals from the teaching experience and research, regarding emancipatory relationships among teachers and students based on the use of group and collaborative relational and communicative practices. From the standpoint of historical and cultural references, the article insists on the need to dismantle the traditional culture of universities, and to develop intersubjective practices based on respect, symmetry in relationships, affectivity, and collaboration. The feasibility of groups as a foundation for this change in educational institutions is debated. Finally, these proposals, developed from social psychology, are linked to the collaborative learning model.